Energy intake, diet diversity, and nutritional status of preschool-aged orphans among selected institutional care facilities in Metropolitan Manila - Dayapdapan, Jash Augeane E.; Garonita, Tiffany Zaira F.; Go, Abigail Laurice R.
Preschool-aged orphans are at high risk of malnutrition due to underweight, stunting, and wasting among children in the Philippines. However, studies regarding the nutrition of preschool-aged orphans remain underexplored. Explanatory sequential research design was used to examine the association between the nutritional value of meals and the nutritional status of preschool-aged orphans in institutional care facilities (ICFs) in Metropolitan Manila. Nutritional status was assessed using Weight-for-Age Z-scores (WFA), and dietary intake was evaluated for macronutrient and micronutrient content. Thirty-two children from four ICFs were recruited through purposive sampling. Results indicated that 31% were underweight. Despite exceeding dietary energy recommendations, dietary diversity scores were below the threshold, with qualitative assessments highlighting a diet high in ultra-processed foods and low in vegetables and organ meats. Both total energy intake and dietary diversity score demonstrated no significant relationship with WFA. The correlation between total energy intake and WFA is weakly positive, while dietary diversity score shows no correlation with WFA. Thematic analysis unveiled meal management challenges that could impact the nutritional status of children, such as the proficiency of food managers in meal preparation and planning. To enhance the nutritional well-being of the children, it is recommended to consult with registered nutritionist-dietitians, implement structured meal plans, and augment nutrition education for caregivers, all aimed at improving their nutritional status.